Autoimmune disease aggregation in families with primary Sjögren's syndrome (2006)
Objective. Diverse autoimmune diseases may coexist in the same individual and in families, implying a common etiology. We examined the aggregation of autoimmune diseases among first-degree relatives (FDR) of patients with primary Sjögren's syndrome (pSS). Methods. This was a population-based case-control family study in which 101 families of women classified as having pSS according to the revised American-European criteria and 124 families of matched controls without autoimmune disease were enrolled to investigate the presence of autoimmune diseases. We performed a genetic analysis that included familial correlation and recurrent risk ratios. Results. In family cases, 38% had at least one FDR with an autoimmune disease, versus 22% in control families [odds ratio (OR) 2.2, 95%) confidence interval (CI) 1.2-3.9, p = 0.01]. An autoimmune disease was registered for 7.3% of 876 patients' FDR as compared with 3.85% of 857 controls' FDR (OR 1.97, 95% CI 1.28-3.03, p = 0.002). The most frequent autoimmune diseases registered among the pSS patients' FDR were autoimmune thyroid disease (AITD), systemic lupus erythematosus, and rheumatoid arthritis, which disclosed aggregation. The proband phenotype (i.e., pSS) was correlated with AITD, systemic sclerosis, and all autoimmune diseases when considered together as a trait. Maternal transmission of the autoimmunity trait was observed in cases but not in controls. Conclusion. Our results indicate that autoimmune diseases cluster within families of patients with pSS. This familial aggregation of autoimmune diseases adds further evidence that clinically different autoimmune phenotypes might share common susceptibility gene variants, which acting in epistatic pleitropy may represent risk factors for autoimmunity.